PROGRAM PEMBELAJARAN AL-QUR’AN DI SMII NURUL MUSTHOFA - Muhammad Badruddin Zarkasyi; Joko Subando (LPPM STAI Muhammadiyah Probolinggo, 2026)
The Al-Qur'an learning program is a strategic educational effort aimed at developing students' ability to read, memorize, and practice the values of the Qur'an in their daily lives. The success of such a program is influenced not only by instructional methods but also by implementation strategies, students' learning motivation, and consistency in maintaining memorization. This study aims to describe the implementation of the Al-Qur'an Learning Program at SMII Nurul Musthofa, focusing on the nature of tahfidz learning, instructional implementation strategies, the dynamics of students' motivation, and efforts to maintain memorization consistency (istiqomah). This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings indicate that the Al-Qur'an learning program was implemented systematically through the stages of planning, implementation, and evaluation. The instructional strategies included the talaqqi, sima'i, murāja'ah, and tajwid methods, supported by continuous evaluation. Students' motivation was strengthened through the integration of intrinsic and extrinsic motivational factors, reinforced by coaching programs, competitions, and reward systems. Memorization consistency was maintained through daily murāja'ah, halaqah activities, the use of mutaba'ah books, and structured time management. Overall, the study concludes that the integration of effective instructional strategies, motivational support, and consistent memorization guidance contributes significantly to improving students' memorization quality while fostering religious values, discipline, and responsibility.